EVALUASI DAN OPTIMALISASI TEKNIK OPERASIONAL PENGELOLAAN SAMPAH KABUPATEN TEMANGGUNG - Muchlis Ridoansyah (Jurnal Teknik Lingkungan, 2012)
Along with the increasing number of urban population and urbanization, it will grow a lot of waste generated as well. According to the Public Works Department, the rate of domestic waste in Temanggung is 2.79 L/person/day, so that waste generation in Temanggung each day is 128m3/day. But the ministry was still 6.27%. To reduce the amount of waste generated in Temanggung had done some trash pemialahan in each house. Given the role of such a society, the waste produced by the settlement will be slightly reduced, where the waste could still be recycled back can still be useful. Based on the need to evaluate the condition of the existing waste management and to the development of waste management system in Temanggung.